The Role of Animation in Developing Interactive Learning for Early Childhood - Arsi, Nabila Afifah; Juhana, Agus (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to explore the role of animation in improving interactive learning in early childhood. In today's digital era, animation is one of the effective media in delivering learning materials in a fun and easy-to-understand way for children. The method used in this study is a qualitative approach with literature studies and participatory observations in several early childhood education institutions. The results of the study indicate that the use of animation in the learning process can improve children's attention, memory, and involvement in learning activities. In addition, interactive animation is also able to stimulate children's cognitive, language, and social development more effectively than conventional methods. The conclusion of this study suggests that the integration of animation in the early childhood learning curriculum can be the right strategy to create a more interesting and meaningful learning experience. And the impact of animation technology on cognitive development, literacy, engagement, and motivation in early childhood. Furthermore, animation-based learning environments have been shown to be effective in developing critical thinking skills, problem-solving abilities, and social skills through collaborative activities. This reinforces the view that the judicious use of animation can bridge digital learning with children's life experiences. Animation has been shown to be a valuable educational tool in modern learning, helping to deepen understanding, improve memory retention, and encourage active participation in the learning process.